USM, KEELE UNIVERSITY SIGNS CO-OPERATION AGREEMENT, STRENGTHENS RELATIONSHIP - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 9 September 2016 – Universiti Sains Malaysia (USM) today signed a cooperation agreement with its strategic partner, Keele University, United Kingdom to further strengthen their longstanding relationship in areas of mutual interest and strength.